Analysis of The Role of Savings and Loans Cooperatives An Effort to MSMEs Case Study on Ksp. Credit Union Harapan Kita - Andre Ramora Sirait; Cece Cece (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
This thesis aims to Analyze the Role of Savings and Loans Cooperatives in Efforts to Improve Micro, Small and Medium Enterprises (MSMEs) Case Studies on KSP. Credit Harapan Kita. This research used a qualitative descriptive method with direct interviews with leaders of KSP: Credit Union Harapan Kita, Field Observations and Documentation. The research results show that saving and loan cooperatives are essential in increasing (MSMEs). Saving and loan cooperatives can provide easy and affordable access to finance for (MSMEs. With that, savings and loan cooperatives can also guide their members in managing their businesses. However, there are several obstacles faced by savings and loan cooperatives in increasing MSMEs. Some of these obstacles include the lack of awareness and understanding of cooperative members in managing loans, limited capital owned by savings and loan cooperatives, and the lack of support from the government and the community in developing savings and loan cooperatives for the public, as well as providing government incentives and support to saving and loan cooperatives can play a more effective role in increasing MSMEs and encouraging economic growth in the Regions